1997
DOI: 10.1152/ajpgi.1997.273.4.g937
|View full text |Cite
|
Sign up to set email alerts
|

Caerulein pancreatitis increases mRNA but reduces protein levels of rat pancreatic heat shock proteins

Abstract: We have recently reported that preconditioning through hyperthermia induces expression of pancreatic heat shock proteins (HSPs) and protects against caerulein pancreatitis. Here, we investigate caerulein-mediated effects on pancreatic HSPs without prior hyperthermia. Caerulein time and dose dependently increased pancreatic mRNA levels of the constitutive isoform of HSP70 (HSC70). However, pancreatic HSC70 protein levels were decreased, as were HSP60 protein levels. Also, in contrast to hyperthermia preconditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
30
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 16 publications
5
30
0
Order By: Relevance
“…4,5) It has been shown that the preinduction of HSP expression has a protective effect against cerulean induced pancreatitis in rats or choline-deficient ethionine-supplemented diet model pancreatitis in mice. 9,10) This observation suggests that the low levels of pancreatic HSPs might be involved in the development of CCK-induced pancreatitis. Rakonczay et al demonstrated that CCK-induced pancreatitis reduces the levels of pancreatic HSPs.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…4,5) It has been shown that the preinduction of HSP expression has a protective effect against cerulean induced pancreatitis in rats or choline-deficient ethionine-supplemented diet model pancreatitis in mice. 9,10) This observation suggests that the low levels of pancreatic HSPs might be involved in the development of CCK-induced pancreatitis. Rakonczay et al demonstrated that CCK-induced pancreatitis reduces the levels of pancreatic HSPs.…”
Section: Discussionmentioning
confidence: 91%
“…But Strowski et al demonstrated that caeruleininduced pancreatitis reduces the levels of pancreatic HSPs. 9) And Rakonczay et al also reported that CCK-induced pancreatitis reduces the levels of pancreatic HSPs. 10) Thus, we checked the effect of statin on HSP 60 expression in acute pancreatitis.…”
Section: Effect Of Statin On Hsp 60 Expression In Cck-induced Acute Pmentioning
confidence: 99%
See 1 more Smart Citation
“…Another suggestion is that hyperthermia might directly prevent the activation of pancreatic enzymes; however, another report showed that kinase activation activity was unaltered after heating procedure (24) ; nevertheless, this issue is controversial and other studies had demonstrated opposite results (4,13) . Another explanation is that the protective effect afforded by hyperthermia could be mediated by HSPs ("heat shock proteins") (35,37) . It is believed that HSPs act as molecular chaperones, making the fi nal folding of other proteins easier and protecting them from additional injuries.…”
Section: Resultsmentioning
confidence: 99%
“…The effect of cerulein is dependent on dose and frequency. The dose and duration of administration are determined according to the required pancreatitis severity (12,13). It has been shown that the administration of cerulein subcutaneously at the dose of 10-20 μg/kg causes acute edematous pancreatitis (14,15).…”
Section: Discussionmentioning
confidence: 99%